2011
DOI: 10.3109/15412555.2010.540272
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Chronic Rhinosinusitis/Nasal Polyp in COPD and Its Effect on the Severity of COPD

Abstract: This study aimed to investigate the effect of chronic rhinosinusitis/nasal polyposis on the severity of COPD and to find out whether the 'united airway disease' hypothesis is valid for COPD. The study enrolled 90 patients diagnosed and staged according to criteria of an international guideline for diagnosis and management of COPD. The patients in stages I and II were classified as Group 1 and the patients in stages III and IV as Group 2. All the patients were questioned about the presence of major and minor cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 24 publications
2
48
1
1
Order By: Relevance
“…Interestingly, there was no significant correlation between SNOT-20 and SGRQ, suggesting that upper and lower airway symptoms independently affect the QoL in COPD patients. The SNOT-20 questionnaire was also used in 90 COPD patients living in Turkey [5]. Sinonasal symptoms were present in 53% and SNOT-20 scores were significantly higher in more severe cases of COPD.…”
Section: Copd Smoking and Sinonasal Quality Of Lifementioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, there was no significant correlation between SNOT-20 and SGRQ, suggesting that upper and lower airway symptoms independently affect the QoL in COPD patients. The SNOT-20 questionnaire was also used in 90 COPD patients living in Turkey [5]. Sinonasal symptoms were present in 53% and SNOT-20 scores were significantly higher in more severe cases of COPD.…”
Section: Copd Smoking and Sinonasal Quality Of Lifementioning
confidence: 99%
“…HURST et al [45], a group from England that has contributed markedly to this area of research over the past 10 years, showed that nasal airway obstruction mirrors the impairment of pulmonary airflow in 51 former and present smokers with mild-severe COPD. In 2011, KELEMENCE et al [5] studied the frequency of sinusitis in patients with COPD; 90 patients (COPD stage I-IV) were included and 48 (53%) had sinusitis. Furthermore, VAN MANEN et al [46] found a strong association between irreversible airway obstruction and sinusitis (OR 6).…”
Section: Copd and Sinonasal Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Hens et al (2008) and Piotrowska et al (2010) found higher endoscopic rhinosinusitis symptom scores in patients with COPD than in the healthy population [6,7]. In 90 patients with COPD in different disease stages, Kelemence et al detected clinical criteria for rhinosinusitis in 53% of the patients [8]. In a review, Kim and Rubin (2007) reported that 75% of all patients with COPD collectively complained of nasal symptoms [9].…”
Section: Introductionmentioning
confidence: 99%